Evaluation of press releases for chronic traumatic encephalopathy research over the last twenty years - Eagle, Shawn R. (Frontiers in Communication, 2026)
Research which associates exposure to repetitive head impacts (RHI) and/or traumatic brain injuries (TBI) with CTE are oft-discussed on social media platforms and tend to get more news coverage in the popular media. One strategy to communicate research findings to the public is by issuing a press release, which reflects a personalized statement about a given study and its importance to the scientific community. The purpose of this study was to investigate the number of press releases published on CTE research over the last 20 years and the rate of publishing press releases by different research entities (i.e., Universities, research institutes, scientific publishers, etc.). Descriptive statistics are provided for the number of press releases for the overall search and by publishing entity. Rates of press releases during the football “season” (August–January) are reported. Of additional interest were the number of press releases published within 1 week of notable professional American football events, such as the Super Bowl, the rookie draft, and combine. Overall, 102 press releases about CTE research were published from October 22nd, 2009 to July 11th, 2025. There were 8 press releases within 1 week of the Super Bowl (7.8%), 9 within 1 week of the rookie draft (8.8%), 5 within 1 week of the combine (5.0%), 46 in the football season (45.1%). Overall, press releases were more likely to meet at least 1 of those criteria than not (n = 67; 65.7% [95% CI: 55.6, 74.8%], p = 0.002). From 2009 (the year of the first published press release) to 2025, Boston University issued a significantly greater proportion of press releases compared to all other institutions combined (n = 50; 49.0% [95% CI: 39.0, 59.1%], p < 0.001). The next most frequent institutions were American Academy of Neurology (n = 7; 6.9%), JAMA Network (n = 6; 5.9%), and Mass General Brigham Hospital (n = 4; 3.9%). Amongst only Universities/research institutions, the most frequent press releases came from Boston University (n = 50; 62.5%), Mass General Brigham Hospital (n = 4; 5.0%), University Health Network (n = 2; 2.5%), and University of California Los Angeles (n = 2; 2.5%). The results of this study show there is a significant disparity in the number of press releases for CTE research across research entities. A disparity this wide in direct press engagements has the potential to create an information monopoly that can skew public understanding. Given the ramifications of CTE research, efforts should be made by multidisciplinary experts to actively join the national conversation and contribute original research on the issue.